Pengaruh Fraud Pentagon, Kepemilikan Institusional dan Asimetris Informasi Terhadap Kecurangan Laporan Keuangan (Studi Empiris pada Perusahaan Perbankan yang Terdaftar Di Bursa Efek Indonesia Tahun 2015-2017) - Mirza Afanin Riandani; Evi Rahmawati (Universitas Muhammadiyah Yogyakarta, 2019)
This study aims to determine how the influence of pentagon fraud, institutional ownership and asymmetric information on financial statements fraud. The pentagon fraud factor studied in this study was financial stability, ineffectiveness of supervision, rationalization, capability and arrogance. The subjects in this study were banking companies listed on the Indonesia Stock Exchange in 2015-2017. The research sample was determined using purposive sampling. This study has a sample of 37 companies with a total of 111 data processed. Data was processed using the SPSS statistical program and analyzed using logistic regression. Based on the results of data analysis, it is known that the variables of financial stability, ineffective monitoring and capability have an effect on financial statements fraud, but rationalization arrogance, institutional ownership and asymmetric information have no effect on the occurrence of fraudulent financial statements.